Drug repurposing of ivermectin abrogates neutrophil extracellular traps and prevents melanoma metastasis - Zhang, Hongjun; Xu, XiaoZhu; Xu, Rui; Ye, Tao (Frontiers in Oncology, 2022)
Neutrophil extracellular traps (NETs) have recently been identified to play a crucial role in cancer metastasis. However, the therapeutic target in NETs of melanoma cancer metastasis is still unknown. In this work, we screened a collection of 231 small molecule compounds. We identified ivermectin (IVM), a widely used antiparasitic drug, significantly inhibits neutrophil extracellular traps (NETs) formation after cathepsin B (CTSB) treatment. In vivo, IVM treatment showed no effects of melanoma tumor growth, while the orthotopic melanoma to lung metastasis was significantly suppressed by IVM. Serum level of myeloperoxidase-DNA and neutrophil elastase-DNA were suppressed after IVM treatment. Tumor infiltrated myeloid-derived suppressor cells (MDSCs) were significantly suppressed while tumor infiltrated CD8+T cells in lung was increased after IVM treatment in mouse melanoma model. Mechanistically, IVM targeted a pyroptotic driving factor gasdermin D (GSDMD), and exhibited a Kd of 267.96 nM by microscale thermophoresis (MST) assay. Furthermore, the direct interaction of IVM and GSDMD significantly suppressed GSDMD oligomerization, which are essential for GSDMD-dependent NETs formation. In vitro, treatment with CTSB in bone marrow neutrophils significantly promotes NETs formation, and the release of extracellular DNA was significantly suppressed by IVM pretreatment. Collectively, our results reveal that with the regulation role of IVM in neutrophils and NETs, IVM may potentially be used as a viable therapeutic approach for the treatment of melanoma cancer metastasis.